(untitled) (Bangladesh Journal of Medical Science, 2018)
Introduction: weakness in case finding and delays in diagnosing patients with smear-positive pulmonary tuberculosis are considered as important factors in spreading disease. According to reports available in some parts of Iran, there is a long delay in diagnosing patients, and case finding level is less than the level predicted by Global Tuberculosis Control Program. Thus, this research was carried out to identify challenges of diagnosing tubercular patients in the framework of Iran’s tuberculosis control program. Methods: Data of present qualitative study was collected through a semi-structured interview. Twenty two informants participated in the study who were selected purposefully. Data were analyzed using framework analysis method. Results: Seventeen subthemes under Six themes regarding challenges of case finding were identified in present study: Policy making and strategies; Human resources issues; Resource availability; Nature of the method used for case finding ;Coordination and communication and Community involvement. Conclusions: Prioritizing tuberculosis control program, providing special allowances for personnel working in this field, active case finding in patients with diabetes and HIV/AIDS, prisoners and homeless people, facilitating access to service-providing centers and making use of novel methods for patients education are among the items efficient on diagnosis of tubercular patients. Bangladesh Journal of Medical Science Vol.17(3) 2018 p.462-469